Implementasi Keadilan Prespektif Islam - Siti Sururin Nasihin Robiati (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2021)
The most basic of social life is justice. The justice in question is the justice recommended by the principles of the Qur'an and Hadith. Justice is also constructed to an ideal truth (morality) and has a great importance for most people (theoretical). This is an anticipation of action in regulating the potential for disputes (small/big). Justice in Islam is expected to include the meaning of equal or equality, balance (proportional), giving rights to the owner and divine justice. This also means that the rulers, officials are essentially also a mandate from God as a form of responsibility to uphold justice. Meanwhile, from the economic aspect that everyone has the same right to obtain a decent and prosperous life based on a sense of divine justice, and a sense of mutual need. This study uses an interpretive analysis with the hope of interpreting a meaning into a normative meaning.